Empirical threshold values of roof connections using pull-out test on nails and screws - Bisa, Harvey O.
Strong typhoons inflict damages in residential house especially on its building envelope (Veron, 2012). One part of the building envelope is the roofing. Due to negative pressures produced by the strong winds, the roofing field is being pulled away and the only type of connection that holds the roofing is its fasteners. The study deals with the determination of threshold values of these connections in Philippines context. Series of experiments were conducted using Instron TM Universal Testing Machine 5980 series. Force vs. displacement graph was simultaneously made by the Bluehill software to determine the behaviour and maximum load. The determination of fastener pullout resistance (FPR) in static loading and cyclic loading test were done. Cyclic loading was patterned and then modified from CSA Loading Sequence (Baskaran, et al. 2008). Combination of roofing, fasteners and purlins were also made to determine the governing modes of failure for the roof connections. Furthermore, the behaviour of series of fasteners was determined by static loading. Based from the results of static loading, wood screw has the strongest FPR (5.6 kN) compared to wood nail and metal screw. Comparing the results of static and cyclic loading, there was 2.8%, 9.4% and 23% decrease in FPR on wood nail, metal screw and wood screw respectively. For combination tests, connections that used wood nail experience pullout, while those connections that used wood screw and metal screw experience tearing in GI sheet. For multiple nail tests, the middle fastener experiences the first pullout on all types of fastener.